2005
DOI: 10.1177/1066480705278467
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Men in Couples Counseling: Strategies for Overcoming Ambivalence and Inexpressiveness

Abstract: Greater attention in scholarly literature has recently been drawn to the unique mental health and clinical needs of men. This article summarizes the existing literature on engaging men in couples counseling. Specifically, strategies are presented to assist counselors to (a) address the help-seeking process for men, (b) assess the role of masculine socialization on presenting concerns and for the process of counseling, and (c) help counselors work with male discomfort with emotions. Clinical examples and vignet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 32 publications
(42 reference statements)
0
47
0
Order By: Relevance
“…Previous research has confirmed that men are typically less likely to seek relationship counselling services than women (Englar-Carlson & Shepard, 2005;Robertson & Fitzgerald, 1992). Despite this reluctance, a growing body of research proposes that men are more receptive to engaging with counselling services during incarceration (Minatrea & Kolbert, 2003;Showalter & Jones, 1980) suggesting that, as with engaging men in prison-based parenting education (Meek, 2007), prison can be an effective context in which to work with men who would be less likely to seek counselling services in a community setting.…”
Section: Introductionmentioning
confidence: 93%
“…Previous research has confirmed that men are typically less likely to seek relationship counselling services than women (Englar-Carlson & Shepard, 2005;Robertson & Fitzgerald, 1992). Despite this reluctance, a growing body of research proposes that men are more receptive to engaging with counselling services during incarceration (Minatrea & Kolbert, 2003;Showalter & Jones, 1980) suggesting that, as with engaging men in prison-based parenting education (Meek, 2007), prison can be an effective context in which to work with men who would be less likely to seek counselling services in a community setting.…”
Section: Introductionmentioning
confidence: 93%
“…Research has shown that relating to and expressing their own emotions can be challenging for some men (Englar‐Carlson & Shepard, 2005; Englar‐Carlson, Stevens, & Scholz, 2010). Counseling work can help men develop the language to understand and communicate their emotional states (Englar‐Carlson & Shepard, 2005).…”
Section: Effective Counseling Practice To Foster Empathy In Menmentioning
confidence: 99%
“…Research has shown that relating to and expressing their own emotions can be challenging for some men (Englar‐Carlson & Shepard, 2005; Englar‐Carlson, Stevens, & Scholz, 2010). Counseling work can help men develop the language to understand and communicate their emotional states (Englar‐Carlson & Shepard, 2005). However, men may also see counseling as an acknowledgement of weakness or as a relational process that does not match their masculine self‐concept (Shepard, 2005; Smiler, 2004).…”
Section: Effective Counseling Practice To Foster Empathy In Menmentioning
confidence: 99%
See 2 more Smart Citations